Coal Growth In The 1970' s -The Key To The Full Energy Future - Carl E. Bagge (Society for Mining, Metallurgy & Exploration, 1972)
It is easy for a coal spokesman to relate to the theme of this meeting--that the decade of the 1970's is pivotal for the mineral industries. For the coal operator, this period is crucial. The coal industry, according to most energy forecasters, must gear its production machinery to meet a sharp rise in the demand for coal--in this decade to sustain inevitable boosts in electricity output, and in the next to start supporting a big new domestic synthetic fuels industry that is already in the formative stage. The logic of that projection flows from a combination of hard circumstances--proved reserves of domestic fluid fuels are dwindling, the hope for bountiful and cheap nuclear power must be indefinitely deferred, and the threat of long-term fuel imports to the national interests is becoming starkly visible. Only coal, with its assets of abundance, security and versatility, offers the nation an adequate and immediate lift out of its current energy crisis. A hard-won expansion of coal production made the critical difference between local power load-shedding and major area blackouts in 1970, the year the energy crisis went public. Coal will have to play that same key role, not just through this pivotal decade but through the turn of the century. But the logic of fuel demand apparently does not always extend to supply. The coal industry has had a huge production job laid out for it by the energy statisticians, but up to now the energy policy-makers have not followed through with the aids and inducements that the coal operator urgently needs to do that job well and completely.